Armadilha BG-Malária: avaliação do efeito da temperatura e da adição de suor humano na captura de anofelinos, com ênfase em Anopheles darlingi Root, 1926 (Diptera, Culicidae) - Leal, Leandro Barros (Instituto Nacional de Pesquisas da Amazônia - INPA, 2014)
Malaria is one of the biggest public health problems. The pathologic agent that causes this disease is transmitted by mosquitoes of the genus Anopheles, which use mostly chemical and physical signals to find blood resources. Therefore, this study's goal was to assess the effect of temperature and human sweat on capturing Anopheles mosquitoes, especially A. darlingi, using a BG-Malaria trap. Traps with CO2 were used in order to compare the attractiveness of different temperature and sweat treatments. In the experiments evaluating temperature, it was used heat light bulbs of different powers. Four treatments were evaluated: (1) CO2 only (control-without light bulb); (2) CO2 + 15V light bulb; (3) CO2 + 40V light bulb; (4) CO2 + 60V light bulb. In order to assess the effect of sweat, eleven treatments were conducted: (1) CO2 only; (2) clean socks; (3) clean shirt; (4) fresh sweat from female foot; (5) incubated sweat from female foot; (6) fresh sweat from female trunk; (7) incubated sweat from female trunk; (8) fresh sweat from male foot; (9) incubated sweat from male foot; (10) fresh sweat from male trunk; (11) incubated sweat from male trunk. White socks and shirts were worn by male and female volunteers in order to collect sweat. Both experiments, with temperature and sweat, underwent a Latin square experimental design, repeated for three times. During the study, 20,775 mosquitoes were collected. Anophelines represented 64.11% (13,320 individuals ) of the sample, while culicines accounted for 35.89% (7,455 individuals). The 13,320 anophelines were collected in three sampling sites during 45 nights, and belong to nine species. A. darlingi was the predominant species in both experiments, accounting for 80.77% of all anophelines collected. In the temperature experiment, the three established temperatures were kept nearly constant. There was congruence between the light bulb voltage and the average temperature reached by them: 24.9 oC in the trap without light bulb; 26.6 oC in the 15V light bulb; 29.7 oC in the 40V, and 31.6 oC in the 60V bulb. Together, the four treatments have captured 4,643 anophelines, distributed in nine species. Among them, A. darlingi was the prevalent species, with 4,431 (95.4%) specimens. According to the results of the three Latin squares performed, for both anophelines in general and A. darlingi alone, there was no significant difference in the mean of captured mosquitoes among the four treatments. Conversely, there was a significant difference among the sampling sites in the second Latin square. In the human sweat experiment, 8,677 anophelines were captured, represented by eight species present in all treatments. Among them, A. darling was the most abundant one, with 6,328 (72.9%) specimens. Similarly to the temperature treatment, there was no significant difference in the mean of captured mosquitoes among the sweat treatments, for both anophelines in general and A. darlingi. Nevertheless, the incubated sweat from both male and female trunk always captured more mosquitoes. Additionally, there was a difference in the mean of captured mosquitoes among the sampling sites.
Keywords: Malária; Anofelinos; Anopheles darlingi